2019
DOI: 10.18502/kss.v3i11.4015
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception on Classroom Action Research

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Works of literature have documented that the teachers have conducted action research for several rationales. Some do the research as a part of their prescribed inservice training, while some others do it due to fulfilment of career promotion (Wulandari et al, 2019). However, the present study revealed that the EFL teachers continued conducting TAR since they believed that they could do something for the success of their students.…”
Section: Factors Affecting Self-directed Tarmentioning
confidence: 55%
See 2 more Smart Citations
“…Works of literature have documented that the teachers have conducted action research for several rationales. Some do the research as a part of their prescribed inservice training, while some others do it due to fulfilment of career promotion (Wulandari et al, 2019). However, the present study revealed that the EFL teachers continued conducting TAR since they believed that they could do something for the success of their students.…”
Section: Factors Affecting Self-directed Tarmentioning
confidence: 55%
“…Only teachers who chose to continue doing action research were selected. This consideration was due to the fact that many teachers did action research as a formality to get a higher rank, and some, in fact, did falsification research reports (Wulandari et al, 2019). In order to select the participants who fulfilled the requirements as mentioned previously, a questionnaire was distributed to ensure that the participants experience the intended phenomenon i.e., the experience of doing action research.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research focuses on the issue of students in a classroom. Wulandari et al, (2019) This study was carried out in SMP N 1 Raya, with 33 students from class VIII D as the participants. The study's quantitative data were gathered from the score of a vocabulary test.…”
Section: Methodsmentioning
confidence: 99%
“…This research is a classroom action research that is generally defined as a teacher's scientific project through a particular model or method to capture phenomena in the classroom (S.A. et al, 2011;Wulandari et al, 2019). The classroom action research design used refers to the Kemmis and McTaggart models.…”
Section: Methodsmentioning
confidence: 99%